Is a separate monotherapy indication warranted for antiepileptic drugs?. Issue 12 (December 2015) - Mintzer, Scott; French, Jacqueline A; Perucca, Emilio; Cramer, Joyce A; Messenheimer, John A; Blum, David E; Rogawski, Michael A; Baulac, Michel
Summary: Antiepileptic drugs (AEDs) are the only neurotherapeutics for which regulatory approval is consistently separated into monotherapy or adjunctive-therapy indications. Because head-to-head comparisons of AEDs (used in the European Union to approve drugs for monotherapy) have not shown substantial differences in efficacy between drugs, FDA approval for use of an AED as monotherapy has typically been based on trials with novel designs that have been criticised for reasons of ethics and clinical relevance. Many new-generation AEDs have not been approved for monotherapy, causing drug labelling and real-world use to be increasingly inconsistent, with negative consequences for patients. The regulatory requirement for separate monotherapy and adjunctive-therapy indications in epilepsy is unnecessarily restrictive. We recommend that regulatory agencies approve AEDs for the treatment of specific seizure types or epilepsy syndromes, irrespective of concomitant drug use.